Endogenous information acquisition and partial announcement policy - Hiroki Arato; Takeo Hori; Tomoya Nakamura (Osaka University, Institute of Social and Economic Research (ISER), 2014)
We extend the model of Cornand and Heinemann (2008, Economic Journal) and examine how to implement partial announcement by selling public information when the agents' action is strategic complements. In a game of information acquisition, there exist multiple equilibria and the partial announcement equilibrium is unstable if the authorities sell public information at a constant price. However, if the authorities offer an increasing pricing rule, partial announcement equilibrium is stable and implementable.
Keywords: C73; D82; D83; E5; 330; Beauty contest games; Transparency of information; Partial announcement policy